EBER in situ hybridization in subcutaneous aluminum granulomas/lymphoid hyperplasia: A diagnostic clue to differentiate injection‐associated lymphoid hyperplasia from other forms of pseudolymphomas and cutaneous lymphomas. (11th February 2021) - Frings, Verena G.; Roth, Sabine; Rosenwald, Andreas; Goebeler, Matthias; Geissinger, Eva; Wobser, Marion
Abstract: Background: Subcutaneous vaccination or desensitization may induce persistent nodules at the injection sites. Without the knowledge of prior injection, histopathological work‐up may be challenging. Objective: Aim of this study was to contribute to the histopathological work‐up of unclear subcutaneous nodules, especially their differentiation from cutaneous lymphoma. Methods: We retrospectively reviewed clinical data and histopathological slides of four patients with subcutaneous nodules, which were suspected to suffer from cutaneous T‐ or B‐cell lymphoma. Sections of these cases and 12 negative controls were stained with hematoxylin and eosin and a standardized immunohistochemical panel of B‐ and T‐cell markers including EBER in situ hybridization as well as electron microscopy. Results: In all cases, large histiocytes with granular cytoplasm compatible with intracellular aluminum hydroxide were present. EBER in situ hybridization revealed positive staining of these granular histiocytes while staining was absent in negative controls. Limitations: Post hoc completion of medical history revealed that vaccination or specific immunotherapy had been applied before at the biopsy site in only three out of four patients; one patient was lost to follow‐up. Conclusion: EBER in situ hybridization is an adjunctive tool to differentiate aluminum‐induced granuloma/lymphoid hyperplasia from other forms of pseudolymphoma and cutaneous B‐ or T‐cell lymphomas.